KONTEKSTUALISASI HUKUM KEADILAN DALAM QISHAS - Muchsin, Agus (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2011)
This article describes the problem in Qishas contextualisation Justice. Assessment results obtained from the understanding that the term